2017
DOI: 10.3126/on.v15i1-2.18789
|View full text |Cite
|
Sign up to set email alerts
|

ELISA validation and determination of cut-off level for chloramphenicol (CAP) residues in shrimp and fish

Abstract: An analytical validation of enzyme-linked immunosorbent assay (ELISA) screening for detection of chloramphenicol (CAP) in shrimp and fish was conducted according to the Commission Decision 2002/657/EC and guidelines for the validation of screening methods for residues of veterinary medicines. The analyte was extracted from shrimp and fish with ethyl acetate mixture, and CAP concentrations were measured photometrically at 450 nm. The recovery rate of the analyte from spiked samples was 80%. For the laboratory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The antibiotic drug chloramphenicol with molecular formular (C11H12CL2N2O5) and molecular weight (323.126g/mol) is one of the antibiotic drugs used widely in the farming of aquatic animals to treat diseases and increase productivity (Sarwer et al, 2017). It is used in most cases for prophylactic and therapeutic conditions in aquaculture because of its broad-spectrum activities against gram negative and gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The antibiotic drug chloramphenicol with molecular formular (C11H12CL2N2O5) and molecular weight (323.126g/mol) is one of the antibiotic drugs used widely in the farming of aquatic animals to treat diseases and increase productivity (Sarwer et al, 2017). It is used in most cases for prophylactic and therapeutic conditions in aquaculture because of its broad-spectrum activities against gram negative and gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Among the four Upazilas of Bhola district, highest number of ponds (11760) were found in Bhola Sadar which occupied 2352 acre area and the lowest number (4250) was found in Tazumuddin Upazila with an area of 1290 acre. Sarwer et al [6] found that the total area of pond was 0.67 acre in Subarnachar Upazila. Pond types: It was found that in study area, 57.30% ponds were used for fish culture, whereas 26.52% and 16.18% ponds were cultivable and derelict respectively (Table 2).…”
Section: Structural Characteristics Of Fish Pondsmentioning
confidence: 99%
“…Standard solutions of Chloramphenicol, AOZ, AMOZ, AHD, and SEM were prepared from the stock solutions according to protocol provided (Sarwer et al, 2017). ELISA (Enzyme Linked Immunosorbent Assay) was applied to determine the level of antibiotic residues in the collected samples (Sarwer et al, 2017). AOZ (type R3703) and AMOZ (R3711), AHD (NF3463), SEM (NF3461) and ELISA kit with chloramphenicol were purchased.…”
Section: Standard Solutions Preparation For Elisamentioning
confidence: 99%